Association of serum irisin levels with body composition, metabolic profile, leptin, and adiponectin levels in lean and obese children - BATIREL, SAİME (My University, 2023)
Background and Objectives: Irisin is an adipo-myokine with potential metabolic effects in the body, and its association with childhood obesity is still controversial. This study aimed to investigate the relationship between serum irisin levels and anthropometric parameters, body composition, metabolic profiles, leptin, and adiponectin in obese and normal-weight children. Methods: The study sample consisted of a total of 80 children aged 6–10, including 44 obese children (BMI ≥ 97th percentile) and 36 normal-weight children. Anthropometric parameters were measured. Body composition was determined with the use of the Bioelectrical Impedance Analysis (BIA) method. Metabolic profiles, as well as irisin, leptin, and adiponectin levels, were analyzed. Results: Anthropometric parameters and body composition were found to be significantly different between the obese and normal-weight groups (p < 0.05). Fasting blood glucose, insulin, HOMA-IR, and leptin levels were found to be significantly higher in the obese group, while the normal-weight group had significantly higher HDL cholesterol and adiponectin levels (p < 0.05). Serum irisin levels did not differ between the obese and normal-weight groups, or based on sex, vitamin D levels, and insulin resistance status. There was also no statistically significant correlation between serum irisin levels and anthropometric parameters, metabolic profile, leptin, and adiponectin. Conclusions: The study concluded that the obese children who participated in this study had high leptin levels and low adiponectin levels, with no significant difference in the irisin levels between the groups. More comprehensive clinical studies are needed to investigate the relationship between irisin and adipokines in children.
Keywords: childhood obesity; irisin; adiponectin; leptin; vitamin D